الدلالات الزمنية للفعل المضارع في اللغة العربية: سورة يوسف غوذخا - Lubna Abd. Rahman (Universiti Sains Islam Malaysia, 2024)
The study attempts to find out the elements that would make the Imperfect Verb, which normally indicates the present and future and to divert from these two tenses to tenses such as the past tense and so forth. It focuses the indications of the Imperfect Verb by analyzing the usage of the verb in the Qar'anic Surah of Yusuf. Following a descriptive and analytical approach, this study found that there are two major elements that determine the indications of tense in the Imperfect Verb. The first element is the role of the context itself and the second is the particles that associate with the verb, such as adverbs and conjunctions. In general, tense in Arabic is indicated either by context or the use of particles.